The Role Of The Marsad Contract In Rehabilitating Degraded Awqaf Lands: Innovative Waqf Projects - ذيب, أحمد (Journal of King Abdulaziz University: Islamic Economics, 2024)
This research is part of an active endeavor to develop endowment (waqf) properties and strengthen confidence in their economic and social potential. It explores the concept of "Marsad contract" as One of the most significant developmental mechanisms that can be adopted for the reconstruction and restructuring of endowment lands.Marsad (designated money) is a debt owed at the endowment, where the lessee invests their own funds with the permission of the administrator of the endowment (Nazir) to develop the essential endowment properties. It is a specialized form of lease that combines two transactions: firstly, a debt owed to the endowment represented by what the lessee (debtor) provides for the development of the endowment property, and secondly, the lease of the endowment to the lessee to benefit from it until the value of that development is consumed.The central issue addressed by this research is precisely the effectiveness of the Marsad contract in the reconstruction and restoration of the endowment lands. To answer this main question, the research proposes a series of subsidiary questions: •What is the nature of the Marsad contract? What is its precise adaptation from a jurisprudential perspective? •What are the limits of the investor's disposal with endowment land? •What are the most important proposed strategies for utilizing this type of contract and strengthening confidence in it? Based on these methodological inquiries, the paper is structured around two pillars: -Theoretical: Defining the Marsad contract, its adaptation from a jurisprudential perspective, and highlighting its most significant economic benefits. -Applied: The research suggests four practical projects: solar energy farms, drought-resistant fruit trees, industrial cluster localization, and strengthening the endowment techniqual.The research concludes by appreciating the developmental returns of this contract and considering it, if implemented with the necessary juristic and legal conditions, as a safe and suitable financial solution for fruitage of endowment lands.